Approximate Solutions for Alcohol Consumption Model in Spain - Sabaa, Mahdi A.; Mohammed, Maha A.; Hatif Abd Almjeed, Sinan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this paper, our aim is to solve analytically a nonlinear social epidemic model as an initial value problem (IVP) of ordinary differential equations. The mathematical social epidemic model under study is applied to alcohol consumption model in Spain. The economic cost of alcohol consumption in Spain is affected by the amount of alcohol consumed. This paper refers to the study of alcohol consumption using some analytical methods. Adomian decomposition and variation iteration methods for solving alcohol consumption model have used. Finally, a compression between the analytic solutions of the two used methods and the previous actual values from 1997 to 2007 years is obtained using the absolute and relative errors. The analysis results obtained have been discussed tabularly and graphically.